Pengaruh Penerapan Sistem Coretax Dan Kualitas Layanan Coretax Terhadap Kepatuhan Wajib Pajak Orang Pribadi Yang Terdaftar Di KPP Pratama Wilayah Kota Palembang - Prastiwi, Ade Maura; Hertati, Lesi; Syafitri, Lili (Badan Penerbit Universitas Muria Kudus, 2026)
This study aims to examine the effect of Coretax system implementation and service quality on the compliance of individual taxpayers registered at KPP Pratama offices in Palembang. A quantitative approach was employed by collecting data through online questionnaires distributed to 100 individual taxpayers who have used the Coretax system during the 2025 period. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4. The results indicate that Coretax implementation and service quality have a positive and significant effect on taxpayer compliance, with an R-square value of 0.757, indicating that the independent variables explain 75.7% of the variance in taxpayer compliance. These findings highlight the importance of integrating digital tax systems with user-oriented service quality to enhance compliance and provide implications for strengthening digital tax policy aimed at improving taxpayer compliance.